Application of a New Schiff Base as Modifier of Octadecyl Silica Membrane Disk for Solid Phase Extraction and Determination of Ultra Trace Nickel(II) from Natural Water and Food Additives - Hossein Mashhadizadeh, Mohammad; Shamspur, Tayebeh; Sheikh Shoaie, Iran (Asian Journal of Chemistry, 2010)
A simple, rapid and cost effective pre-concentration method is described for the determination of trace amount of nickel(II) in water and food samples by flame atomic absorption spectrometry. The method is based on sorption of nickel(II) ions on octadecyl bonded silica membrane disk modified with a new Schiff base bis[5-((4 nitrophenyl)azo salicylaldehyde)] and then eluted with HCl and determined by flame atomic absorption spectrometry. Extraction efficiency and the pH of sample, optimum amount of Schiff base, type and optimum amount of eluent and flow rates of sample and eluent were evaluated. The analytical figures of merit for the determination of nickel(II) are as follows: pre-concentration factor 100, detection limit (3s) 0.5 ng/mL and precision (RSD) 1.4%. The method has been used for the determination of nickel in natural water samples and in baking powder and soda powder.